Hubungan dukungan keluarga dengan kualitas hidup pasien gagal ginjal kronik yang menjalani terapi hemodialisis di RSUD Sekarwangi - Aziz, Abdul (Jurnal Health Society, 2025)
Background: The quality of life of patients with chronic renal failure will gradually decrease due to regular haemodialysis. One aspect that can improve the quality of life of patients with chronic renal failure is family support. The purpose of this study was to determine the relationship between family support and the quality of life of patients with chronic renal failure undergoing haemodialysis therapy at Sekarwangi Hospital. Method: Type of correlational research with a cross sectional approach. The population was all chronic renal failure patients undergoing haemodialysis therapy at Sekarwangi Hospital with a sample of 132 people. Sampling using total sampling. The research instrument was KDQOL SF-36 for quality of life variables and a questionnaire using a likert scale for family support variables, data collection using a questionnaire and statistical analysis using the Chi-Square test (ꭓ2). Result: The results showed that most patients had supportive family support, namely 113 people (85.6%) and good quality of life, namely 88 people (66.7%), there was a relationship between family support and the quality of life of chronic renal failure patients undergoing haemodialysis therapy at Sekarwangi Hospital with a p-value of 0.000 (<0.05). Conclusion: There is a relationship between family support and the quality of life of chronic renal failure patients undergoing haemodialysis therapy at Sekarwangi Hospital.